(untitled) (Research, Society and Development, 2022)
Drugs are natural or synthetic chemicals that produce changes in the senses. This category can include drugs for pharmacological use or active principles that cause changes in sensory perceptions of space and reality, such as licit and illicit recreational drugs that can affect the user. Some varieties of food for human consumption are considered by various culinary ethnicities, as responsible for the promotion of health or the emergence of diseases. The use in medicine and cooking of spices, fruits and roots is quite old, with purposes of temperance, conservation and restoration of the balance of humors in the body. Currently, the discussion in society is not only whether it is safe or toxic to consume certain foods, but also the amounts ingested and the cooking techniques that are being used to mitigate the undesirable and dangerous compounds that are part of the composition of different groups. of food and that are present in the food routine. This study is an integrative review of the relationship between food, drugs and poisons, seeking their concepts and correlations, aiming at human well-being.